The importance and moral aspects of music in human society and Kurdish society in particular - ڕەشید, بەختیار حسەین (Sulaimani Journal for Humanities, 2019)
Life under music is like nature under the birds Imagine if you walk through a forest and the birds are silent if the birds are so important in beautifying nature and then music is important in decorating human society In our time, music in all its forms is available to every individual throughout society, no matter where he lives in the world. Music is an inseparable part of your life as a human being In the lives of many people, as it is said, music conveys emotional and aesthetic meanings to the ends of the earth, and this immediately raises the important question of why we view music so valuable and important. The view that music is profoundly influential and natural for listeners is not the invention of such research and centuries, but from ancient times to the present day, philosophers have dealt with the importance of music in society They have determined their role in shaping human character and behavior, and it is important that in the view of many philosophers, music has a significant and clear ability to express various human feelings and emotions despite the busy life The importance and necessity of music as a living and repeated art is mainly not research that softens the fingers with the most important views about music, especially philosophical views, nor the view that the effect of music on emotions As a researcher, I discuss the issues from a philosophical, sociological and psychological perspective and try to make all the important interpretations In addition, in the course of this research, I will try to answer some important questions that many of us are involved in, such as why we do music. Why has every culture throughout history had something that plays a role in music? Why does music have such an impact on Nima? How does music shape our character? What does music have to do with morale? What is the relationship between music and pleasure? Finally, in relation to what has been said about this unique art, I will try to answer to show the emotional and moral impact of music on Kurdish society